"People need them or else they're going to take fentanyl and die": A qualitative study examining the 'problem' of prescription opioid diversion during an overdose epidemic. (June 2021) - Bardwell, Geoff; Small, Will; Lavalley, Jennifer; McNeil, Ryan; Kerr, Thomas
Abstract: The practice of prescription opioid (PO) diversion remains highly controversial and has been characterized as a source of significant drug-related harm by physicians and public health officials. We critically analyze the "problem" of diversion through an examination of the perspectives of people who divert POs during an overdose epidemic to better understand the practice, including benefits and challenges, as well as how diversion is shaped by structural contexts. Qualitative semi-structured interviews were conducted with 21 participants recruited from ongoing cohort studies involving people who use drugs in Vancouver, Canada. Prohibitive prescribing policies made accessing POs difficult, leading some to smuggle drugs out of clinics. Others would buy POs in bulk or do trades to acquire them. Participants risked having their prescriptions terminated, but rationalized this risk as a protective measure that allows them to provide safer drugs to others (e.g., to prevent overdose or treat withdrawal). Poverty also framed diversion, with some participants diverting their POs to generate income to pay for expenses including food and sometimes illicit fentanyl (perceived as a stronger alternative). However, diversion was shaped by other constraints, including criminalization, negative health impacts from not consistently consuming POs, and supplies running out, which led some participants to rely on other illegal means to generate income. This study highlights the intricate means by which POs are acquired and diverted and how environmental contexts frame how participants negotiated risk and rationalized diversion. Our study provides an alternative perspective on the "problem" of diversion and demonstrate a positive effect in providing a safer drug supply to others during an overdose crisis. Given that drug policy, criminalization, and poverty created challenges, our findings demonstrate the need for strategies that engender greater safety, reduce harm, and alleviate the effects of these constraints, including through policies promoting safer drug supplies, decriminalization, and employment. Highlights: The "problem" of prescription opioid diversion is examined. Diversion was rationalized as a protective measure for others. Social and structural contexts framed motivations for diversion. Strategies are needed to reduce harms and alleviate contextual constraints. Policies promoting decriminalization and a safer drug supply are needed.